Dual-function transaminases with hybrid nanoflower for the production of value-added chemicals from biobased levulinic acid - Khobragade, Taresh P.; Giri, Pritam; Pagar, Amol D.; Patil, Mahesh D.; Sarak, Sharad; Joo, Sangwoo; Goh, Younghwan; Jung, Seohee; Yoon, Hyunseok; Yun, Subin; Kwon, Youkyoung; Yun, Hyungdon (Frontiers in Bioengineering and Biotechnology, 2023)
The U.S. Department of Energy has listed levulinic acid (LA) as one of the top 12 compounds derived from biomass. LA has gained much attention owing to its conversion into enantiopure 4aminopentanoic acid through an amination reaction. Herein, we developed a coupled-enzyme recyclable cascade employing two transaminases (TAs) for the synthesis of (S)-4-aminopentanoic acid. First TAs were was first utilized to convert LA into (S)-4-aminopentanoic acid using (S)-α-Methylbenzylamine [(S)-α-MBA] as an amino donor. The deaminated (S)-α-MBA i.e. acetophenone was recycled back using a second TAs while using isopropyl amine (IPA) amino donor to generate easily removable acetone. Enzymatic reactions were carried out using with different systems, providing the with conversions ranging from 30 to 80%. Furthermore, the hybrid nanoflowers (HNF) of the fusion protein were constructed which afforded complete biocatalytic conversion of LA to the desired (S)-4aminopentanoic acid. The created HNF demonstrated storage stability for over a month and can be reused for up to 7 sequential cycles. A preparative scale reaction (100 mL) achieved the complete conversion with an isolated yield of 62%. Furthermore, the applicability of this recycling system was tested with different β-keto ester substrates, wherein 18-48% of corresponding β-amino acids were synthesized. Finally, this recycling system was applied for the biosynthesis of pharmaceutical important drug sitagliptin intermediate ((R)-3-amino-4-(2,4,5-triflurophenyl) butanoic acid) with an excellent conversion 82%. This is a provisional file, not the final typeset article agricultural products (Froidevaux et al., 2016). Traditional organo-catalytic or chemical processes, however, frequently call for pricey starting materials and/or transition-metal catalysts, laborious protection and deprotection stages, and high pressures and/or temperatures (Collet et al., 2009). Alternatively, biocatalytic processes are advantageous such as simpler, safer for the environment, more atom-efficient, and highly enantioselective along with some disadvantage like stability which include inactivation at high temperature, solvents, pH value, ionic strength, and salt type (